Edukasi Manajemen Penyusunan Karya Tulis Ilmiah (Skripsi) pada Mahasiswa - Surya Akbar; Ira Cinta Lestari; Tezar Samekto Darungan; Halimah Thania Nasution (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This community service activity was carried out in response to research findings that students who are writing scientific papers often experience stress and anxiety. Therefore, this activity provides education on techniques and methods that can be applied by students to improve their scientific paper writing skills. This educational activity was conducted in the form of a one-day seminar held on the FKUISU campus during June 2025 with 26 student participants. The methods used were education and discussion. The material presented was information literacy skills, time management, and eliminating procrastination behaviour. The results showed that, in general, students were already aware of the techniques or methods of managing the preparation of scientific papers, but were unable to apply them. The activity implementation team assisted students in understanding the techniques and methods they needed to master in accordance with the material presented. Lecturers need to be introduced to these techniques so that they can monitor students' abilities in managing the preparation of scientific papers (theses).